1999
DOI: 10.1001/archfami.8.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Tools to Improve Documentation of Smoking Status: Continuous Quality Improvement and Electronic Medical Records

Abstract: A continuous quality improvement group process aided by an electronic medical record is useful to develop a self-sustaining office system to screen, document, and periodically update smoking status in a consistent place in the medical record. Although screening for and documenting smoking status are only the first step toward helping patients stop smoking, it is an important one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Traditional methods to change provider practice, such as continuing medical education conferences, have met with sobering results. More promising methods include academic detailing or office-based educational outreach (Soumerai & Avorn, 1990), peer-comparison data feedback (Keller, Griffin, Schneiter, Wennberg, & Russell, 2000;Keller, Wennberg, & Soule, 1997), use of reminder systems or computerized tools (Spencer, Swanson, Hueston, & Edberg, 1999), and enhancing office systems for quality improvement (Dietrich et al, 1992;Hollis, Lichtenstein, Vogt, Stevens, & Biglan, 1993). Studies using either academic detailing or data feedback have been shown to decrease unnecessary medication prescribing and laboratory testing for some conditions (Kroenke & Pinholt, 1990;McConnell et al, 1982;Ramoska, 1998); studies using either method to increase the provision of preventive services have had inconsistent findings (Goldberg et al, 1998;Tierney, Hui, & McDonald, 1986;Williams, Eckert, Epstein, Mourad, & Helmick, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods to change provider practice, such as continuing medical education conferences, have met with sobering results. More promising methods include academic detailing or office-based educational outreach (Soumerai & Avorn, 1990), peer-comparison data feedback (Keller, Griffin, Schneiter, Wennberg, & Russell, 2000;Keller, Wennberg, & Soule, 1997), use of reminder systems or computerized tools (Spencer, Swanson, Hueston, & Edberg, 1999), and enhancing office systems for quality improvement (Dietrich et al, 1992;Hollis, Lichtenstein, Vogt, Stevens, & Biglan, 1993). Studies using either academic detailing or data feedback have been shown to decrease unnecessary medication prescribing and laboratory testing for some conditions (Kroenke & Pinholt, 1990;McConnell et al, 1982;Ramoska, 1998); studies using either method to increase the provision of preventive services have had inconsistent findings (Goldberg et al, 1998;Tierney, Hui, & McDonald, 1986;Williams, Eckert, Epstein, Mourad, & Helmick, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Screening the records for smoking status also led to increased smoking cessation counselling for a selected group of smokers in another study [14]. In the intervention centres, 21% (50/241) of the smokers accepted the offer of cessation treatment; 40% (19/47) of these patients reported that they were non-smokers after one year.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts include the growth of practice-based research networks in primary care 37 and the ongoing expansion of continuous quality improvement in health-care settings. 38 …”
Section: Assess the Intervention In Diverse Clinical Practice Settingsmentioning
confidence: 99%